The retrospective survey of oral and maxillofacial malignant neoplasms (Mustansiria Dental Journal, 2018)
Background: Awareness of the epidemiological characteristics of oral cancers allowfor enhanced planning of timely and effective treatment in order to improvepatients’ life quality. Despite the fact that oral and perioral cancers are notincluded in common cancers, they are of special importance for their impact onhuman morbidity and life quality.Aim of the present study was to investigate the distributional patterns of oral andperioral malignancies in terms of age, gender, type and location.Materials and Methods: 4179 Oral and Maxillofacial cases taken over 5 years (2009- 2013) at the Department of Oral and Maxillofacial Surgery, Specialist SurgeriesHospital, Medical city, Baghdad, were studied. Among these, 707 biopsyspecimens were made for histopathological diagnosis, 182 cases included oralmalignant lesions and the rest cases were benign lesions. The data involve age,gender, location, and type of malignancy for these cases were recorded.Results: The results of this survey showed that the most common malignant orallesions were of epithelial origin with 121 cases (66%), salivary lesions with 20cases (11%), and hematogenic malignancies with 18 cases (10%). Squamous cellcarcinoma, adenoid cystic carcinoma and lymphoma were the most commonmalignant lesions in this area of the body. The mean age of patients was (39.1)years of old and the male to female ratio was found to be 1.3:1.Conclusion: In this study, epithelial malignant tumors constituted the majority ofdiagnosed malignant tumors followed by salivary malignant tumors andlymphomas.